Nilai Keterangan Saksi Yang Diajukan Oleh Penggugat dan Tergugat - Paulus Tiku Taru Padang (Universitas Atma jaya Makassar, 2011)
This Papper Adresses the issue of how the value of the testimony of the witnesses presented by the plaintiffs and defendants. The research is conducted with a case study that has been done in the state court of Makale. The purpose of this research is to know the value of the testimony of the witnesses presented by the plaintiffs and defendants. .........................